The potential function of short rotation coppice strips for birds and ground beetles (Coleoptera, Carabidae) - Zehlius-Eckert, W. (2014)
The presented study tries to identify the habitat potential of short rotation coppice strips (SRCs) for birds and ground beetles. The basic assumption of the study is, that the species composition of SRCs in agricultural landscapes is a function of the regional and local species pool, the site conditions, the characteristics of the SRCs (e.g. width and rotation length, age of the SRCs) and species characteristics. The study is mainly based on a literature research. In a first step studies about the establishment of birds and ground beetles in short rotation coppices were analysed. Because most of the studies have researched young short rotation coppices an additional literature research was carried out for birds and ground beetles in hedges. The intention was to get an impression of the long-term development of the species composition. It is assumed, especially for ground beetles, that hedges have a similar species composition as the SRCs. In order to identify the causes for successful establishment of some and the failure of other species to establish, several environmental parameters (e.g. soil moisture and grain size of the soil, age of the hedge), corresponding species characteristics like habitat preferences and flight ability and information about the regional species pools were integrated into the analysis. For the birds the literature research about short rotation coppices was supplemented by an expert assessment. Lists of expected species in SRCs are presented. The list is differentiated geographically and in time (time since establishment and last cutting, respectively) where necessary. For ground beetles the influence of distance to woodlands or other woody habitat, width and area of the hedge and of the mobility of the species for the establishment of woodland species is described.